Synthetic lethality of combined AT-101 with idarubicin in acute myeloid leukemia via blockade of DNA repair and activation of intrinsic apoptotic pathway. (1st October 2019) - Yang, Qianying; Chen, Kai; Zhang, Leisi; Feng, Liying; Fu, Guofeng; Jiang, Shan; Bi, Silei; Lin, Chunjie; Zhou, Yong; Zhao, Haijun; Chen, Xiao Lei; Fu, Guo; et al.
Abstract: Leukemia stem cells (LSCs) are deemed to the mainspring for treatment failure in acute myeloid leukemia (AML). Conventional chemotherapeutic drugs fail to eradicate leukemia stem cells, which becomes the root of drug resistance and disease recurrence. Hence, new therapeutic strategies targeting LSCs are supposed to be critical for patients with AML. Here we report that combination of Bcl-2 inhibitor AT-101 and chemotherapeutic drug idarubicin (IDA) results in synergistic lethality in CD34 + CD38 − leukemia stem-like cells sorted from KG-1α and Kasumi-1 AML cell lines and primary CD34 + AML cells in vitro while sparing the normal counterparts. In addition, combinatorial treatment also significantly inhibits the growth of patient-derived xenograft (PDX) mouse models generated from FLT3-ITD mut AML patient in vivo . Mechanistically, the synergistic effects of AT-101 with IDA to induce cell death are closely associated with blockage of DNA damage repair and thus activates the intrinsic apoptotic pathway. In summary, these findings suggest that combinatorial therapy with AT-101 and IDA selectively eliminates leukemia stem-like cells both in vitro and in vivo, representing a potent and alternative salvage therapy for the treatment of relapsed and refractory patients with AML. Highlights: AT-101 combined with idarubicin shows synergistic killing to AML stem-like cells. AT-101 blocks DNA repair response upon DNA-damaging idarubicin treatment. AT-101/idarubicin depends on the activation of intrinsic apoptotic pathway. AT-101/idarubicin selectively kills primary AML cells while sparing normal cells. AT-101/idarubicin suppresses tumor growth in patient-derived xenograft mouse models.